Evaluation Of Cardiac Specific Marker Cardiac Troponin I After Coronary Bypass Surgery (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background: Cardiac troponin I (cTnI) is reported to be very specific for myocardial cell damage  without cross reactivity with skeletal muscle isoform. Evaluation of cTnI after CABG will be useful  as an early marker of excessive post operative myocardial damage when a specific therapeutic  intervention can still be efficient and improve outcome. Methodology: The study comprised of 50 patients who undergo Coronary artery bypass surgery  at V.S group of Hospital. Blood sample were taken after 12 hour ( T12) and 24 hour ( T24 ) of post  CABG. The sample were analysed for cTnI. Results: Our results show that Troponin I levels after 2 hours, 12 hours and 24 hours in patients  who had better outcome after CABG was 9.2 ng/ml, 13.9 ng/ml and 10.9 ng/ml respectively.  Whereas, Troponin I levels after 2 hours, 12 hours and 24 hours in patients who had adverse  outcome like death of patients after CABG was 10.6 ng/ml, 38.7 ng/ml and 28.9 ng/ml respectively. Conclusion: Routine measurement of cardiac troponin levels after cardiac troponin can identify  group of patients at increased risk of complications or death.
Keywords: Cardiac Troponin I (cTnI ); Coronary artery bypass grafting (CABG); Post operative myocardial infarction (PMI)